High-resolution profile of neoantigen-specific TCR activation links moderate stimulation to increased resilience of engineered TCR-T cells - Franziska Füchsl; Johannes Untch; Vladyslav Kavaka; Gabriela Zuleger; Sarah Braun; Antonia Schwanzer; Sebastian Jarosch; Carolin Vogelsang; Niklas de Andrade Krätzig; Dario Gosmann; Rupert Öllinger; Piero Giansanti; et al. (Nature Communications)
Abstract Neoantigen-specific T cell receptors (neoTCRs) promise safe, personalized anti-tumor immunotherapy. However, detailed assessment of neoTCR-characteristics affecting therapeutic efficacy is mostly missing. Previously, we identified diverse neoTCRs restricted to different neoantigens in a melanoma patient. In this work, we now combine single-cell TCR-sequencing and RNA-sequencing after neoantigen-specific restimulation of peripheral blood-derived CD8+ T cells of this patient. We detect neoTCRs with specificity for the previously detected neoantigens and perform fine-characterization of neoTCR-transgenic (tg) T cells in vitro and in vivo. We describe a heterogeneous spectrum of TCR-intrinsic activation patterns in response to a shared neoepitope ranging from previously detected more highly frequent neoTCRs with moderate activation to rare ones with initially stronger activation. Experimental restimulation of adoptively transferred neoTCR-tg T cells in a xenogeneic rechallenge tumor model demonstrates superior anti-tumor responses of moderate neoTCR-tg T cells upon repeated tumor contact. These insights have significant implications for the selection of TCRs for therapeutic engineering of TCR-tg T cells.